The shapes we need - Rowland, Kurt F. (New York Van Nostrand Reinhold, 1965)
Discusses how the shapes of man-made objects reflect the technological achievement, functional awareness, and "visual language" of a particular society and era
Keywords: Design, Industrial; Design